The Influence of the Work Environment and Work Discipline on Nurse Performance with Motivation as a Mediating Variable at "JIH" Hospital Yogyakarta - Harwanti, Indah; Subyantoro, Arief; Hikmah, Khoirul (Strata International Journal of Social Issues, 2025)
This study examines the influence of the work environment and work discipline on nurse performance, with motivation as a mediating variable, at “JIH” Hospital Yogyakarta. Nurses play a critical role in healthcare service delivery, making their performance a key determinant of hospital quality and patient satisfaction. Despite structured performance evaluations, challenges such as inconsistent responsiveness and disciplinary lapses remain. Previous research presents mixed findings on the effects of work environment and discipline, as well as the mediating role of motivation, suggesting the need for further empirical investigation within the unique context of sharia-based healthcare institutions. Using a quantitative explanatory approach, data were collected from 76 permanent nurses selected through simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that both work environment and work discipline have a positive and significant impact on nurse performance. Motivation significantly mediates these relationships, with work discipline contributing more strongly to motivational enhancement than the work environment. These findings highlight the importance of integrating effective disciplinary policies, supportive work environments, and strategic motivation management.